Forms of specialist knowledge applied in the criminal investigation of offences in the field of economic activity - V. O. Usatii (Bulletin of Kharkiv National University of Internal Affairs)
The article substantiates that the scientific literature uses various concepts to denote the ways in which specialist knowledge is used in the course of criminal investigations. The generalization of the Ukrainian scholars’ theoretical approaches made it possible to argue for the expediency of using the concept of “form of use of specialist knowledge”, since it indicates not only the external expression of such activity, but also covers the objective and subjective conditions in which specialist knowledge is implemented, as well as the legal framework which determines the procedural procedure for its application.